KEWENANGAN YANG DIMILIKI OLEH PENYIDIK DALAM TINDAKAN MENYURUH BERHENTI ORANG YANG DI CURIGAI (TINJAUAN PASAL 5 HURUF A, ANGKA 3 KUHAP) - WIDODO, MUHAMMAD TAUFIK (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACT            The Authority That Owned By Investigators In Action To Stop A Suspected Person ( Consderation to Article 5, No. 3 KUHAP ). Under the Guidance by Mr. Abdul Rokhim And Mrs. Lily Erlianti.            The purpose of the study is to know how the investigators get a warran to do the authority to stop a person that suspected and how about the person want to to the order from the investigators.            The research used the methodology normative or research literature, where research normative law is a procedure scientific research to found the truth according to the logic science rhat sees from the normative sides. The caracteristic on this thesis writing is descriptive analysis, that meant to explain the problem of the study and then for doing the analyze to get the conclusion.            According to this research can be summarize that the investigators action to do the authority in order to stop a person to stop being suspected and asking and also to check the identity that added to Article 5 Letter E No. 3 Constitution the criminal law, doesn’t need the warrant from the higher or investigatord can take an action to arrest the suspected person, after the investigators had the evidence that strong enough to be proof and appropriate with Article 184 KUHAP and also orientation to PERKAB (According to the Police Chief No. 1 year 2009 ) about use the strength in police action .  Keyword : Investigator, Proposionalitas, Profesionalism.